Understanding culture: the voices of urban Aboriginal young people. (26th November 2021) - Murrup-Stewart, Cammi; Whyman, Theoni; Jobson, Laura; Adams, Karen
ABSTRACT: Culture is an essential factor in the wellbeing of Indigenous peoples, but colonisation has disrupted and fragmented Indigenous cultures across the world. In Australia, urban Aboriginal young people are a growing population. However, research, policies and programmes aimed at improving Aboriginal wellbeing are unclear in their understanding of what culture is and how it is included in practice, particularly from the perspective of urban Aboriginal young people. Therefore, this study used yarning and thematic analysis to explore the experiences and conceptualisations of culture from the perspective of young, urban Aboriginal people. The young people described culture in terms of relationships, connection to Country, shared beliefs and values, and with regards to identity. Such understanding will contribute to an evidence-base of appropriate, better targeted and more effective wellbeing policies and programmes.